Model Project Based Learning Meningkatkan Kreativitas dan Keterampilan Berwirausaha Siswa Saat PJJ - Zuniarti (Jurnal Riset Daerah, 2021)
The purpose of the research is to find out how is the process of implementing the project based learning model in increasing creativity and skills in making student business products, how are the results of increasing students' creativity and skills in making business products through a project based learning model in the lesson of creative products and entrepreneurship for class XII culinary 4 SMKN 1 Sewon 2020/2021. This research is a classroom action research (CAR) with a project based learning model. The research subjects were students of class XII Catering 4 at SMK Negeri 1 Sewon, totaling 31 students. Implementation from July to October 2020, consists of 3 cycles, with the stages: "Observation, Planning-Action & Reflection". Actions are carried out by researchers and collaborators who are tasked with observing and recording every development. The data collection method used is observation. Data analysis was carried out by measuring the creativity and skills of the culinary business products, namely by presenting in the form of tables and percentages. The results showed that the initial observations of many groups were still less creative and skilled. Through the application of the project based learning (PJBL) method. In the application of the project based learning (PJBL) method, students experience an increase in their creative thinking and skills after being given action. Increased creativity in making student business products in learning creative products and entrepreneurship for class XII Culinary 4 SMKN 1 Sewon 2020/2021 by 67.85%, and increasing skills in making student business products by 54.84%. The description above shows that the project based learning (PJBL) method can improve students' creativity and skills in learning creative products and entrepreneurship.